Productivity of three varieties of local upland rice on swidden agriculture field in Setulang village, North Kalimantan, Indonesia - OKTIANI PERIDA MERANG; Abubakar M. Lahjie; SYAHRIR YUSUF; YOSEP RUSLIM (Society for Indonesian Biodiversity, 2020)
Abstract. Merang OP, Lahjie AM, Yusuf S, Ruslim Y. 2020. Productivity of three varieties of local upland rice on swidden agriculture field in Setulang village, North Kalimantan, Indonesia. Biodiversitas 21: 49-56. Swidden agriculture field is a dry land used by traditional farmers to cultivate some varieties of local upland rice intercropped with vegetables, tubers, and fruits. This rotational cultivation system utilizes the land for planting such food crops in one year period before it is left for fallow periods for years. This study aimed to assess the productivity of local upland rice varieties (i.e. Langsat rice, Telang Usan rice, and Pimping rice) cultivated on swidden agriculture field in regard to the fallow periods. This study was conducted in Setulang village, Malinau District, North Kalimantan Province and employed purposive sampling method using interviews of selected respondents and field observation. Among three varieties of rice in this study, Langsat rice had the longest fallow period with 17 years while Pimping rice had the shortest fallow period with 13 years, with the maximum production were 2,635 kg ha-1 and 1,670 kg ha-1, respectively. Meanwhile, Telang Usan rice reached the maximum production on fallow period of 15 years with the total production of 2,208 kg ha-1. Overall, of the three types of rice planted, the results show that the longer the fallow period, the higher the rice production and the shorter the fallow period, the lower the production. Each type of rice has a different amount of production, although it is planted during the same fallow period.